Haematological toxicities with immunotherapy in patients with cancer: a systematic review and meta-analysis. (November 2018) - Petrelli, Fausto; Ardito, Raffaele; Borgonovo, Karen; Lonati, Veronica; Cabiddu, Mary; Ghilardi, Mara; Barni, Sandro
Abstract: Introduction: Programmed cell death-1 or ligand 1 (PD-(L)1) inhibitors are associated with immune-related adverse events. Conversely, little is known about the incidence of haematological toxicities across published trials. We have performed a systematic review and meta-analysis to evaluate the incidence of immunotherapy-related anaemia, neutropenia and thrombocytopenia among different tumour types, trials phases and anti-PD-(L)1 agents. Material and methods: A PubMed, Embase and Cochrane library search on 23rd December 2017 and a review of references from relevant articles were done. Studies regarding haematological diseases were excluded. The pooled incidence rates weighted for the individual sample sizes were calculated according to fixed or random effect models. Incidence of all-grade and grade (G) III or higher anaemia were the primary end-points. Neutropenia, febrile neutropenia and thrombocytopenia were secondary end-points. Results: Forty-seven studies of PD-(L)1 inhibitors for a total of 9324 evaluable patients were included in the meta-analysis. The overall incidence of anaemia during PD-(L)1 inhibitor was 9.8% (95% confidence interval [CI], 6–13.6%) for all-grade and 5% (95% CI, 3.3–6.7%) for G3-5 anaemia. The incidence was higher in diseases different from genitourinary, lung and melanoma, with avelumab and in phase II studies. In randomised trials, relative risk of all-grade anaemia for patients receiving anti-PD-(L)1 agents compared with control arms was 0.25 (95% CI, 0.16–0.39; p < 0.001). Incidence of all grades and G3-5 neutropenia and thrombocytopenia were 0.94%, 1.07%, 2.8% and 1.8%, respectively. Febrile neutropenia was 0.45%. Conclusions: The incidence of PD-(L)1 inhibitor-related anaemia was not negligible. Severe neutropenia, thrombocytopenia and febrile neutropenia were rare. These findings are useful for clinicians and suggest that blood cell count should be checked before every cycle and support should be given when severe toxicity appears. Highlights: Incidence of PD-[L]1 inhibitor's haematological toxicity is presently unknown and under-reported. We have performed a systematic review and meta-analysis of 47 trials among solid tumours. Anaemia, neutropenia, febrile neutropenia and thrombocytopenia were 9.8, 0.9, 2.8 and 0.4%. The risk of anaemia with anti-PD-(L)1 agents is not negligible, while that of neutropenia was rare. Clinicians should check the complete blood cell count before every cycle of therapy.